Top-down approaches to layered transition metal dichalcogenides and oxides green production and to their use in electrochemical energy conversion and storage - Crisci, Matteo; Justus Liebig University Giessen (My University, 2024)
Energy consumption has increased in recent years, and in our current society, it is expected to grow even more. However, concerns about how the energy is produced are also rising, since we can currently observe issues resulting from past reckless policies. To solve the issues, many countries are shifting towards the production of energy through renewable sources, which, while being a promising way to solve the energy crisis, also have significant problems. One of the main ones is their intermittency, meaning they have periods with high energy production and other where it is much lower. To address this issue, energy storage devices are key to store excess energy in peak production periods and releasing it when necessary. Super-capacitors are quite interesting from this point of view, due to their good energy and power density, allowing for fast charge and discharge, whilst also providing a good amount of energy, making them suitable for quick energy access and backup power sources. Among the material used for such devices, 2D materials are used, providing high surface area and stability, but suffering from restacking and poor capacitance. On the other hand, another interesting class of materials is Conductive Polymers (CPs) which showcases very high specific capacitance, but are always victims of rapid performances degradation. Therefore, the combination of these two materials can lead to a general improvement of their properties and solving their individual issues. The focus of this thesis’ work is to produce and lay the basis for further work on the use of blends using 2D material, specifically MoS2 and WS2 and conductive polymers. To do so, the first part of the thesis is aimed at the production of 2D materials using different solvents and techniques and establishing a characterization protocol. While the second focuses on the actual production of the blends using 2D-TMDC and PANI and their structural and electrochemical characterization in both three and two-electrode set up.
Keywords: 2D Materials; Supercapacitors; Electrochemistry; Material Science; Liquid Phase Exfoliation; Exfoliation; Conductive Polymer; ddc:540